Lipid-modified oligonucleotide conjugates: Insights into gene silencing, interaction with model membranes and cellular uptake mechanisms - Ugarte-Uribe, B; Grijalvo, S; Pertíñez, SN; Busto, JV; Martín, C; Alagia, A; Goñi, FM; Eritja, R; Alkorta, I (Elsevier, 2016)
The ability of oligonucleotides to silence specific genes or inhibit the biological activity of specific proteins has generated great interest in their use as research tools and therapeutic agents. Unfortunately, their biological applications meet the limitation of their poor cellular accessibility. Developing an appropriate delivery system for oligonucleotides is essential to achieve their efficient cellular uptake. In the present work a series of phosphorothioate lipid–oligonucleotide hybrids were synthesized introducing covalently single or double lipid tails at both 3′- and 5′-termini of an antisense oligonucleotide. Gene transfections in cultured cells showed antisense luciferase inhibition without the use of a transfecting agent for conjugates modified with the double-lipid tail at 5′-termini. The effect of the double lipid-tailed modification was further studied in detail in several model membrane systems as well as in cellular uptake experiments. During these studies the spontaneous formation of self-assembled microstructures is clearly observed. Lipidation allowed the efficient incorporation of the oligonucleotide in HeLa cells by a macropinocytosis mechanism without causing cytotoxicity in cells or altering the binding properties of the oligonucleotide conjugates. In addition, both single- and double-tailed compounds showed a similar behavior in lipid model membranes, making them useful in nucleotide-based technologies.